Almost everywhere convergence for sequences of pairwise NQD random variables. Issue 5 (4th March 2017) - Yang, Weiguo; Zhu, Daying; Gao, Rong
ABSTRACT: In this article, we are going to study the almost everywhere convergence for sequences of pairwise negatively quadrant dependent random variables by using truncation technique and Kolmogorov-type generalized three-series theorem. Our results generalize and improve the corresponding results of Wu (2002 ) and Li and Yang (2008 ). We also give some examples showing that our extensions are not trivial.